ARTIFICIAL INTELLIGENCE AS A FACTOR IN THE EVOLUTION OF MODERN LANGUAGE AND THE FORMATION OF STUDENTS’ LANGUAGE COMPETENCE (Uzbekistan Open Conference, 2025)
The article examines the influence of artificial intelligence on language, foreign language learning, and youth communication. It explores how AI affects vocabulary, grammar, and speech style, supports the development of all components of language competence, and aids in preparation for international language exams. Special attention is given to its role in fostering critical thinking, analytical skills, and communicative flexibility among young people. Both the opportunities and limitations of these technologies are analyzed, as well as the necessity of combining AI with pedagogical guidance for effective and conscious learning.